Flowering and fructification phenology in macadamia integrifolia (2009)
In the rural area of Timbío, located in the Cauca region of Colombia, an area of 287 ha is planted with different varieties of macadamia (Macadamia integrifolia), which still have not realized their full potential. In this research, the phenology of the flowering and fructification of five macadamia varieties: HAES 294, HAES 344, HAES 741, HAES 788, HAES 800 was evaluated. Forty inflorescences per variety were selected in order to determine: inflorescence period, number of flowers/inflorescence, number of fruits/bunch and fruit diameter. Additionally, the most important phenological stages of the two processes were defined. Flower growth lasted between 57 and 62 days, and the inflorescence had five stages: flower buttons, differentiation of flower units, end of growth, flower opening and pollination. Differences in the inflorescence period were statistically significant and ranged from 10.7 to 15.7 cm, with the HAES 788 variety having the longest inflorescences and the HAES 800 variety the shortest. The number of flowers/inflorescence ranged from 89 to 135: HAES 800 had the fewest and HAES 294 the most. The biggest fruits were obtained from HAES 788, HAES 800 and HAES 294 with an average diameter of 3.1 cm, and the smaller fruits, with a 2.8 cm average diameter were obtained from HAES 344 and HAES 741. Three stages were identified: fruit tie-up, morphologic development and physiological maturity; the duration of which ranged from 210 to 234 days. The average number of fruits/bunch for HAES 344, HAES 294, HAES 788 and HAES 741 ranged from 3.2 to 3.9, and for HAES 800 was 1.2 fruits/bunch.